Iris Analysis for Biometric Recognition Systems - Bodade, Rajesh M.; Talbar, Sanjay N.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2014)
The book presents three most significant areas in Biometrics and Pattern Recognition. A step-by-step approach for design and implementation of Dual Tree Complex Wavelet Transform (DTCWT) plus Rotated Complex Wavelet Filters (RCWF) is discussed in detail. In addition to the above, the book provides detailed analysis of iris images and two methods of iris segmentation. It also discusses simplified study of some subspace-based methods and distance measures for iris recognition backed by empirical studies and statistical success verifications.
Introduction to Iris Recognition -- Related Work -- Iris Segmentation -- Iris Recognition using Dual Tree Complex Wavelet Transform and Rotated Complex Wavelet Filters -- Conclusion and Future Scope.
Keywords: Engineering; Pattern recognition; Biometrics (Biology).; Computational intelligence; Engineering; Signal, Image and Speech Processing; Biometrics; Computational Intelligence; Pattern Recognition